Ceramic-on-ceramic catastrophic liner failure in total hip arthroplasty: Morphological and compositional analysis of fractured ceramic components - Bistolfi, Alessandro; Ferracini, Riccardo; Lee, Gwo Chin; Mellano, Danilo; Guidotti, Claudio; Baino, Francesco; Verné, Enrica (Ceramics international, 2021)
Surface bearing of total hip arthroplasty (THA) still is a strong subject of study due to the relatively high rate of failures caused by a multiplicity of factors including surgical technique, patient's attitude, and type/characteristics of the materials used (metal, ceramics, polyethylene) with their specific risk factors. Fractures of the ceramic components are rare but catastrophic events, with many concerns among the orthopaedic surgeons. Such complication is usually evaluated from a clinical viewpoint; this study provides a materials scientist's complementary perspective and comprehensively evaluates the surface and the mechanism of rupture of the ceramic liner in two cases with different ceramics (Biolox Forte and Biolox Delta) after ceramic-on-ceramic THA. The morphological and compositional analyses of the ceramic components were performed by field-emission scanning electron microscopy (FESEM) and energy dispersive spectroscopy (EDS), along with macroscopic pictures. The SEM analysis of the ceramic liner showed many wear signs in all directions, while the EDS revealed the presence of titanium near to the fracture border, which might be interpreted as a consequence of the catastrophic contact between ceramic liner and metal back. Biolox Delta and Biolox Forte ceramic liners showed different patterns of fracture and surface modifications that are illustrated and discussed.